Can novel methods be useful for pain assessment of castrated piglets?. (5th January 2015) - Lonardi, C.; Scollo, A.; Normando, S.; Brscic, M.; Gottardo, F.
Abstract : Given that surgical castration is a painful practice performed on millions of pigs every year, a need to identify novel reliable pain assessment tools exists in order to test anaesthetic and analgesic protocols that may reduce related pain. Two treatments were considered: handling (H) and surgical castration (C). Physiological (cortisol, lactate, glycaemia, rectal and eye temperature) and behavioural variables (latency to move after treatment and alterations in posture and walking) were analysed. Cortisol showed the greatest level in C piglets within 20 min after the surgical procedure and a positive correlation with glucose concentration. Eye temperature was higher in C piglets, and the same difference was detected for rectal temperature 3 h after castration. Behavioural parameters revealed that C piglets had longer latency to move and a higher percentage of them showed alterations in posture and walking. Results of this study showed that, in castrated piglets behavioural and physiological alterations occur mainly in the first 3 h from treatment. Latency to move, alterations in posture and walking, and eye temperature appear to give additional and useful information in piglet pain assessment. However, differently from the behavioural parameters considered, eye temperature involves several manipulations of the animals and a long process to acquire the data.